So many remainders

For any natural number n n ,let's define a sequence < R i > <R_{i}> such that R 100 R_{100} is the remainder obtained when n n is divided by 100. R 99 R_{99} is the remainder when R 100 R_{100} is divided by 99. R 98 R_{98} is remainder when R 99 R_{99} is divided by 98 and so on.

Find the least value of n n for which,

H = 1 < i < = 100 R i + 1 < i < j < = 100 R i R j + ( 1 < i < j < k < = 100 ( R i R j R k ) ) + . . . + R 2 R 3 R 4 . . . . . R 100 \displaystyle H= \sum_{1<i<=100} R_{i}+\sum_{1<i<j<=100} R_{i} R_{j}+(\sum_{1<i<j<k<=100}( R_{i} R_{j} R_{k}))+...+R_{2}R_{3}R_{4}.....R_{100} attains its maximum possible value


If you are looking for more such simple but twisted questions, Twisted problems for JEE aspirants is for you!


The answer is 23.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Mark Hennings
Jan 23, 2017

Suppose that R 100 = m R_{100} = m , where 0 m 99 0 \le m \le 99 . It is a simple induction (working down from 100 100 ) to show that R j = { m j m + 1 0 j m R_j \; = \; \left\{ \begin{array}{ll} m & j \ge m+1 \\ 0 & j \le m \end{array} \right. (so long as we are dividing by a number greater than m m , m m yields remainder m m . Dividing m m by m m gives remainder 0 0 , and dividing 0 0 by anything gives remainder 0 0 ). Thus H + 1 = j = 2 100 ( 1 + R j ) = ( m + 1 ) 100 m H+1 \; = \; \prod_{j=2}^{100} (1+R_j) \; = \; (m+1)^{100-m} which is maximized when m = 23 m=23 . The smallest positive integer value of n n for which R 100 = 23 R_{100} = 23 is, of course, 23 \boxed{23} itself.

To see why m = 23 m=23 gives the maximum, the function f ( x ) = ln ( x 101 x ) = ( 101 x ) ln x x > 0 f(x) \; = \; \ln\big(x^{101-x}\big) \; = \; (101-x)\ln x \hspace{2cm} x > 0 has derivative f ( x ) = 101 x 1 ln x f'(x) \; =\; \frac{101}{x} - 1 - \ln x which is a strictly decreasing function, with f ( 24 ) > 0 > f ( 25 ) f'(24) > 0 > f'(25) . Thus f ( x ) f(x) has a single maximum at a point α \alpha , where 24 < α < 25 24 < \alpha < 25 , and since f ( 24 ) > f ( 25 ) f(24) > f(25) we see that f f is maximised over the integers at x = 24 x=24 . This gives the answer of m = 23 m=23

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...